2014
DOI: 10.3109/00365513.2014.954141
|View full text |Cite
|
Sign up to set email alerts
|

Gamma glutamyl transferase activity is Independently associated with oxidative stress rather than SYNTAX score

Abstract: In stable CAD, increased GGT activity within the normal range is associated with increased oxidative stress rather than increased extent and complexity of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…It has been reported that GGT is a marker for oxidative stress and inflammation and positively associated with inflammatory markers including C reactive protein, IL-6 and IL-1β 21. Increased visceral fat is accompanied by increased production of proinflammatory adipokines and cytokines such as IL-6 and Plasminogen activator inhibitor-1 19.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that GGT is a marker for oxidative stress and inflammation and positively associated with inflammatory markers including C reactive protein, IL-6 and IL-1β 21. Increased visceral fat is accompanied by increased production of proinflammatory adipokines and cytokines such as IL-6 and Plasminogen activator inhibitor-1 19.…”
Section: Discussionmentioning
confidence: 99%
“…The serum concentration of gamma-glutamyl transpeptidase (γ-GTP) could act as a marker of oxidative stress [2, 3], and oxidative stress has been reported to play a crucial role in the pathogenesis of both of atherosclerosis [4] and hypertension [5]. As aging is also known to be associated with oxidative stress [6, 7], γ-GTP could act as a marker of risk factor in age-related disease such as atherosclerosis and hypertension in elderly subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Serum GGT activity is regarded as an early marker of antioxidant inadequacy, even within the reference range generally accepted [44, 45]. In this study, PDL women have shown a higher GGT activity compared to those from Lisbon, which was correlated with all aminothiols, mainly GSH.…”
Section: Discussionmentioning
confidence: 50%